Aging voice: presbyphonia - Garcia Martins, Regina Helena [UNESP]; Goncalves, Tatiana Maria [UNESP]; Benito Pessin, Adriana Bueno [UNESP]; Branco, Anete [UNESP] (Springer, 2014)
Presbyphonia is a physiological process of aging voice that includes morphological changes in the coverage mucosa, muscle, and cartilage. We revised the morphological, endoscopic, and vocal acoustic changes that occur in presbyphonia and discussed some treatments proposed to minimize glottal incompetence and improve vocal performance of the elderly.
Keywords: Presbyphonia; Voice; Elderly; Dysphonia; Aging